Effect of adenoidectomy in children with complex problems of rhinosinusitis and associated diseases - Kitirat Ungkanont (2018)
Objective: The effectiveness of adenoidectomy in the management of pediatric sinusitis is still a controversial issue. The size of the adenoid and associated diseases are the factors for consideration. The adenoid has been studied and is proved to be a probable source of infection for the paranasal sinus. The purpose of this study is to evaluate the efficacy of adenoidectomy in reducing the frequency of sinusitis in children. Methods: A prospective study was done in pediatric patients with rhinosinusitis admitted for adenoidectomy from January 2000 to January 2002. Pre-operative frequency of rhinosinusitis, underlying diseases and the diseases caused by the adenoid were recorded. The adenoid size was evaluated by lateral skull X-ray. The patients were followed after surgery and frequency of rhinosinusitis and associated diseases were compared with the pre-operative period. Results: There were 37 patients with mean age of 6±2.8 years. Mean duration for pre-operative review was 436.7 days and mean duration for post-operative follow up was 450.2 days. Almost all (92%) of the patients had obstructive sleep disorder and 88.2% had adenoid-nasopharyngeal ratio >0.7. There was a statistically significant reduction of episodes per year of rhinosinusitis and obstructive sleep disorder after surgery (P-value < 0.001 and 0.008, respectively). Conclusion: Adenoidectomy was proved to be effective in the management of pediatric rhinosinusitis in this series. Adenoidectomy should be most beneficial as a surgical option before endoscopic sinus surgery (ESS), especially in younger children with obstructive symptoms. © 2003 Elsevier Ireland Ltd. All rights reserved.